FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN METODE KONTRASEPSI IMPLANT DIKLINIK SARI ADITYA LOKA II, BUNGO TAHUN 2021 - Hendry Wibowo; Sylvi Nezi Azwita (Sekolah Tinggi Pariwisata Mataram, 2022)
The Indonesian government has launched various programs to deal with existing population problems. One of the programs with national planning as an integral part of national development whose family has a goal is to encourage PUS (Pupes of Childbearing Age) to take part in the Family Planning Program (BKKBN 2016). This type of research is a quantitative analytic study using a cross sectional approach where the method of returning data on the independent variable and the dependent variable is taken at one time at the same time which aims to determine the factors that influence the use of the implant contraceptive method at the Kencana Clinic Office. DPPKB Bungo Regency in 2021. Based on the research that has been carried out with Chi Square statistical tests with 163 respondents, it was found that respondents aged 30-35 years who chose contraceptive implants were 71 people with KB Implants 31 people (30.9%) p-value 0.003 where p < 0.05, moderate parity respondents who chose Implant KB contraception as many as 76 people with KB Implant 32 people (33.1%) p-value 0.007 where p < 0.05, respondents who graduated from high school/MA 77 people, who used KB Implant 33 people (33.5%) p-value 0.005 where p <0.05, respondents who work formally 78 people, who use KB Implant 34 people (34.0%) p-value 0.007 where p <0.02 , there is a significant relationship between age, parity, education, and health factors with implant contraceptive methods. For DPPKB, to add references and input materials in making policy planning to increase public participation in the use of contraceptive methods